1994
DOI: 10.1017/s1357729800042582
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body weight and energy intake on the composition of deposited tissue in pigs

Abstract: Many pig growth models assume that there is no effect of energy intake and of body weight on the ratio of lipid to protein deposition rate in pigs below their maximal protein deposition rate. An experiment was performed to check whether an effect of body weight and of amount of energy intake on this partitioning of energy is indeed absent when protein deposition is limited by energy intake. Two constant amounts of energy were given above maintenance requirement (12·6 and 16·3 MJ digestible energy (DE) per day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
3
18
1
Order By: Relevance
“…In our experiment, an increase in fat content and fat deposition rate, along with the highest ME levels, was observed; which indicated that above 3,264 kcal ME, there was a surplus of energy higher than requirements for protein deposition; also, the excess resulted in fat storage. The same result was found by Greef et al (1994) who observed that above maximum capacity of protein deposition, the high daily energy intake caused increase in the carcass's lipid:protein ratio. Being the pigs from the dam line hybrids, their maximum capacity of protein deposition was achieved at 3,264 kcal of ME/kg or less.…”
Section: Resultssupporting
confidence: 83%
“…In our experiment, an increase in fat content and fat deposition rate, along with the highest ME levels, was observed; which indicated that above 3,264 kcal ME, there was a surplus of energy higher than requirements for protein deposition; also, the excess resulted in fat storage. The same result was found by Greef et al (1994) who observed that above maximum capacity of protein deposition, the high daily energy intake caused increase in the carcass's lipid:protein ratio. Being the pigs from the dam line hybrids, their maximum capacity of protein deposition was achieved at 3,264 kcal of ME/kg or less.…”
Section: Resultssupporting
confidence: 83%
“…An age effect was detected for growth and carcass parameters (P < 0.01); the decrease in growth rate of pigs older than 8 mo is in agreement with the wellknown effect of the increase in age and slaughter weight on pig performance (De Greef et al, 1994;Whittemore 1994;Candek-Potokar et al, 1998). Previous research studies performed on heavy pigs (Bittante et al, 1990;Franci et al, 1994a) did not show consistent differences in growth rate between pigs slaughtered at different ages and weights, but the dietary regimens were not reported and the compared slaughtering weights were lower than in the present trial (110 to 145 and 131 to 159 kg, respectively, vs. 143 to 182).…”
Section: Growth Performance and Carcass Compositionsupporting
confidence: 82%
“…The ratio between lipid and protein deposition (LD: PD) increased curvilinearly from approximately .5 at the lowest intake level to 2.2 at the higher intake levels. This increase in LD:PD with increasing energy intake has been reported earlier for young and older pigs (Campbell et al, 1983b;De Greef et al, 1994;Bikker et al, 1995). Nevertheless, it is often assumed that below PD max the LD:PD is constant and independent of energy intake.…”
Section: Effect Of Energy Intake Between 45 and 85 Kilogramssupporting
confidence: 78%